Complexation and coacervation of polyelectrolytes with oppositely charged colloids - Kizilay, Ebru; Kayitmazer, A. Basak; Dubin, Paul L. (Advances in colloid and interface science, 2011)
Polyelectrolyte-colloid coacervation could be viewed as a sub-category of complex coacervation, but is unique in (1) retaining the structure and properties of the colloid, and (2) reducing the heterogeneity and configurational complexity of polyelectrolyte–polyelectrolyte (PE–PE) systems. Interest in protein-polyelectrolyte coacervates arises from preservation of biofunctionality; in addition, the geometric and charge isotropy of micelles allows for better comparison with theory, taking into account the central role of colloid charge density. In the context of these two systems, we describe critical conditions for complex formation and for coacervation with regard to colloid and polyelectrolyte charge densities, ionic strength, PE molecular weight (MW), and stoichiometry; and effects of temperature and shear, which are unique to the PE-micelle systems. The coacervation process is discussed in terms of theoretical treatments and models, as supported by experimental findings. We point out how soluble aggregates, subject to various equilibria and disproportionation effects, can self-assemble leading to heterogeneity in macroscopically homogeneous coacervates, on multiple length scales.